2018
DOI: 10.1111/ijlh.12905
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an immunochromatographic strip test for alpha‐thalassaemia screening

Abstract: The ICT is simple to perform, with higher sensitivity than HbH-i, and gives the result in a short time and at a lower cost. This can be used by clinical laboratories to replace HbH-i for α-thalassaemia detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Regarding sample stability, our results are in agreement with Bunkall et al who demonstrated that there was no difference between ICT results at 24 hours and 7 days. The age of the false‐positive results was not statistically different to that of the true negatives, suggesting that false positives cannot be attributed to sample age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding sample stability, our results are in agreement with Bunkall et al who demonstrated that there was no difference between ICT results at 24 hours and 7 days. The age of the false‐positive results was not statistically different to that of the true negatives, suggesting that false positives cannot be attributed to sample age.…”
Section: Discussionsupporting
confidence: 93%
“…Limitations of the ICT include the potential for false‐positive results with elevated HbF and in neonates. Bunkall et al demonstrated that it could be used from 6 months of age, but until this time genetic studies would be required to diagnose an alpha gene abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…However, using the i+LAB α THAL IC strip test, 3 α 0 -thalassemia (-- SEA ) samples showed a negative result. As Hb Bart’s has also been demonstrated as a marker for α 0 -thalassemia traits [21, 2527], the negative samples in this study may be false negatives. It is worth noting that these 3 samples showed a very faint band in the T line zone but were designed as negative.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, the IC ζ strip test for detecting ζ-globin chains was validated in parallel with the commercialized IC strip test for detecting Hb Bart’s (i+LAB α THAL IC strip test [21, 2527].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation